Performance evaluation of secure multipath retransmission mechanism in next generation heterogeneous communication systems. Issue 2 (1st March 2018) - Zeng, Jiaxin; Cao, Yuanlong; Ke, Fenfen; Huang, Minghe; Zhang, Guanghe; Lu, Wei
Abstract : With the standardisation of the fifth generation (5G) wireless network interface was established in 3GPP, the features of 5G arouse great interest both in academics and industry, even government. The significant advancements of 5G wireless network technology will make a great increase in the demand for content‐rich streaming media services. What's more, many mobile devices with heterogeneous network interfaces (4G, WiFi, and even 5G) connect multiple paths for data delivery simultaneously. Multiple Transmission Control Protocol (MPTCP) is recommended by Internet Engineering Task Force (IETF) to multi‐path parallel transmission, which is an important transport layer protocol. Although there are many attractive benefits by using MPTCP for data delivery, it becomes sensitive for MPTCP to network attacks. When a subflow with the MPTCP association suffers from some network attacks (e.g. denial of service attacks), there is undoubted that it will cause large numbers of retransmission data. Unfortunately, the regular MPTCP retransmission mechanisms retransmit data over the same path, which may cause receiver buffer blocking. In this study, the authors propose effective retransmission mechanisms in MPTCP for retransmitting data on a non‐congested path. The simulation results show that the proposed retransmission mechanism has better performance than the regular' in the network attacks.